Pancreatic Arteriovenous Malformation Presenting with Upper Gastrointestinal Bleeding: Treatment with Transarterial Embolization—A Case Report - S. Vignesh; Abdulla K.V; Haris K.P; Satheesh Vasudevan; Athulya Balan (Journal of Clinical Interventional Radiology ISVIR)
Pancreatic arteriovenous malformations (AVMs) are a rare entity among visceral AVMs and less common cause of gastrointestinal bleeding. We report a case of pancreatic AVM in a 45-year-old man who presented with upper gastrointestinal bleeding and duodenal ulcers, and was hemodynamically unstable. Ultrasound and computed tomography (CT) of the abdomen showed multiple dilated arterial channels in the head region of the pancreas, arising from the gastroduodenal artery, with early filling of the portal vein, suggestive of an AVM. Transarterial embolization was performed by selectively embolizing the arterial feeders using poly-vinyl alcohol (PVA) particles. Postembolization, obliteration of the AVM was seen. On follow-up 2 months later, the patient was clinically stable.